Hypercholesterolemia and Lymphatic Defects: The Chicken or the Egg? - Miyazaki, Takuro; Miyazaki, Akira (Frontiers in Cardiovascular Medicine, 2021)
Lymphatic vessels are necessary for maintaining tissue fluid balance, trafficking of immune cells, and transport of dietary lipids. Growing evidence suggest that lymphatic functions are limited under hypercholesterolemic conditions, which is closely related to atherosclerotic development involving the coronary and other large arteries. Indeed, ablation of lymphatic systems by Chy-mutation as well as depletion of lymphangiogenic factors, including vascular endothelial growth factor-C and -D, in mice perturbs lipoprotein composition to augment hypercholesterolemia. Several investigations have reported that periarterial microlymphatics were attracted by atheroma-derived lymphangiogenic factors, which facilitated lymphatic invasion into the intima of atherosclerotic lesions, thereby modifying immune cell trafficking. In contrast to the lipomodulatory and immunomodulatory roles of the lymphatic systems, the critical drivers of lymphangiogenesis and the details of lymphatic insults under hypercholesterolemic conditions have not been fully elucidated. Interestingly, cholesterol-lowering trials enable hypercholesterolemic prevention of lymphatic drainage in mice; however, a causal relationship between hypercholesterolemia and lymphatic defects remains elusive. In this review, the contribution of aberrant lymphangiogenesis and lymphatic cholesterol transport to hypercholesterolemic atherosclerosis was highlighted. The causal relationship between hypercholesterolemia and lymphatic insults as well as the current achievements in the field were discussed.